(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In the article we will consider the issues of increasing the thermal efficiency of solar air heaters by artificially interrupting the hydrodynamic boundary layer in the heater channels. Intensification models and formulas for calculating heat transfer are proposed.